Genetic connections and antimicrobial resistance in dogs and owners Staphylococcus pseudintermedius isolates - Martins, Christina Resende; de Melo, Roberta Torres; Bastos, Clara Mariano; Rosa, Rafaela Oliveira; Pereira, Amanda Gubert; Figueiredo Braz, Raquelline; Loures, Gabriela de Paiva; Fonseca, Belchiolina Beatriz; Buiatte, Ana Beatriz Garcez; Heinemann, Marcos Bryan; Viana, Marcus Vinicius Canário; Aburjaile, Flávia Figueira; et al. (Frontiers in Veterinary Science, 2025)
The study’s objective was to isolate Staphylococcus pseudintermedius from dogs with superficial pyoderma and/or recurrent otitis, and their guardians, to determine oxacillin, cefovecin, and gentamicin resistance, associated risk factors for infection, and genetic similarity between isolates from dogs and guardians. Prevalence of S. pseudintermedius in dogs was 76% and in humans was 56%, with concurrent identification in 44%. Oxacillin resistance occurred in 6.38% of dog isolates and 11.36% of isolates from guardians, with relatively strong (disk diffusion test) or moderate (Minimum Inhibitory Concentration) association between phenotypic testing and mecA gene presence. For cefovecin, dog isolates presented resistance in 8.15% disk diffusion and 23.40% broth microdilution. In humans, 6.81 and 36.36% showed cefovecin resistance in disk diffusion and Minimum Inhibitory Concentration tests. Gentamicin resistance in dogs was identified in broth microdilution testing in 2.12%. fnbB was identified in 4.39% of isolates with relatively strong association between results of dogs and humans. Dogs sleeping with S. pseudintermedius-positive humans were 6 times more likely to test positive, and dogs attending grooming sessions were 4 times more likely positive for S. pseudintermedius. The whole genome sequencing revealed transmission between dogs and humans in 3 cases. Resistance genes for 8 antibiotic classes were found in chromosomal and plasmid genomes.